Accumulation of Biopesticide-Based Rotenone from an Optimized [BMIM][OTf] Green Binary Solvent Mixture in Different Parts of Terong Plant (Solanum Melongena). (2016) - Kang, Ho Yong; Othman, Zetty Shafiqa; Zubairi, Saiful Irwan
Abstract: Infestation of pests on the field crops has resulted losses on its productivity yearly. Moreover, over usage of pesticides has also affected consumer's health as pesticides residues are detected inside the post-harvested crops. Therefore, the aim of this study is to determine the accumulation of rotenone Derris sp. in leaves, stem and fruit of terong plant ( Solanum melongena ) through the degradation rate (k) and half-life (t1/2 ) of sprayed rotenone extract. The sprayed rotenone was prepared by using an optimized binary solvent mixture of 95% (v/v) acetone and ionic liquid (1-butyl-3-methylimidazolium trifluoromethansulfonate [BMIM] [OTf] via normal soaking extraction method. The same extraction method was used on the plant parts by using only 95% (v/v) of acetone. Reverse-phase high performance liquid chromatography (RP-HPLC) was used in analysing rotenone and [BMIM][OTf] traces. The results indicate that the degradation rates of 20 ppm were (1.35 ± 0.02 day -1 for leaves; 1.89 ± 0.07 day -1 for fruit) faster than 1000 ppm of rotenone extract (0.24 ± 0.00 day -1 for leaves; 0.21 ± 0.01 day -1 for stem; 0.31 ± 0.01 day -1 for fruit) ( p <0.05) within 6 days of observation. Rotenone was identified to possess the half-life (t1/2 ) in the range of 0.37 ± 0.01 day to 0.51 ± 0.01 day in the study of 20 ppm rotenone extract. In contrast, the half-life (t1/2 ) for rotenone on 1000 ppm extract was in the range of 2.23 ± 0.05 days to 3.38 ± 0.10 days which was longer than 20 ppm extract ( p <0.05). In conclusion, rotenone extract is still considered safe and has the potential to be used as a bio-pesticide due to its shorter half-life (t1/2 ) (less than 7 days at the highest concentration of 1000 ppm) than other commercial pesticides.